The location of thrush nests on buildings affects the chance of cowbird parasitism - Batisteli, Augusto Florisvaldo; Pizo, Marco Aurélio [UNESP] (Asociacion Espanola de Ecologia Terrestre (AEET), 2022)
Nest site placement is a critical choice among passerines, being an important factor that affects their breeding success. In urban areas, human buildings offer suitable nesting sites usually less exposed to predators and brood parasitic birds and readily available to be reused for several breeding seasons. However, the extent to which the features of nest placement sites in buildings contribute to reduce nest detectability by predators and brood parasites is still unknown. Here, we tested whether the features of the nesting site (i.e., lateral concealment, distance to the building ceiling, and height above ground) affect the chance of brood parasitism by Shiny Cowbirds (Molothrus bonariensis) in Pale-breasted Thrushes (Turdus leucomelas) nests placed on buildings in a Brazilian suburban area from 2013 to 2019. Cowbird parasitism increased throughout the study years, and nests closer to ceilings, supposedly better concealed, were more likely to be parasitized. Laying date, height above ground, and lateral concealment were not related to the probability of cowbird parasitism. We suggest that less concealed nests enhance vicinity monitoring by parents, allowing a faster agonistic response to the presence of cowbirds near the nest. Our results indicate that nest site location in cities may have consequences for the breeding success of cowbird hosts.
Keywords: anthropogenic nesting sites; Molothrus bonariensis; nest concealment; urban bird